AYURVEDIC MANAGEMENT OF ASTHI-MAJJAGATA VATA W.R.T. ANKYLOSING SPONDYLITIS THROUGH PANCHATIKTA KSHEERA BASTI-A CASE REPORT - Dr MELODY LAISHRAM; DR SANGEETA H TOSHIKHANE; DR NISHA RATHVA (The Bioscan, 2025)
Ankylosing spondylitis(AS) is a chronic inflammatory disease of the spine that often leads to vertebral fusion limiting movement, causing stiffness of spine and a forward stooped posture. In Ayurveda, we can co-relate with asthi-majja gata vata whereby similar symptoms of AS are found that are asthi-parva bheda, sandhi shula, mamsa bala kshaya1, santata ruja2 sandhi. Clinical studies have shown the importance of Ayurveda and Panchakarma in the management of AS. In this case study, a female patient aged 40 years age diagnosed with AS 2 years back was presenting typical symptoms of lumbar AS such as chronic low back pain, stiffness, difficulty in walking,etc. She was treated with panchatikta ksheera basti for 16 days alongside oral medications . Main assessment criteria before and after the intervention was BASDAI(Bath Ankylosing Spondylitis Disease Activity Index) scale founded by Calin et al., Bath, 1994, Range of motion of the lumbar spine and VAS(Visual Analog Scale). Patient showed significant relief in lumbosacral pain, reduced intensity, tenderness and duration of morning stiffness, reduced levels of ESR and CRP. Thus, this case supports the prominent role of Ayurveda in the management of AS through Panchakarma.